Законодавча регламентація затримання особи без ухвали слідчого судді - Маник, О. В.; Manyk , O. V. (Європейські перспективи. - 2017. - № 3. - С. 234-240, 2017)
Підкреслено, що на сьогодні можна назвати доволі значну кількість нормативно-правових актів, приписи яких встановлюють правові підстави затримання особи без ухвали слідчого судді. Наголошено на важливості встановлення сутності правових підстав затримання особи без ухвали слідчого судді та здійсненні аналізу провідних з них.

In this article, it has been emphasized that today it is possible to name a fairly significant number of normative legal acts, the prescriptions of which establish the legal grounds for detaining a person without a decision of an investigating judge. The importance of establishing the essence of the legal grounds for detaining a person without a decision of the in vestigating judge and carrying out an analysis of the leading ones has been emphasized. An analysis of the substantive components of the “legal basis” category has been carried out. It has been proved that such a meaningful component as “right” within the studied category should be considered from the standpoint of its subjective and objective understanding. The author’s vision of the essence of the legal grounds for detaining a person without a decision of the investigating judge has been formed. It has been argued that the analysis of normative legal acts, at the level of which the legal grounds for detaining a person without a decision of the investigating judge are fixed, must be carried out by classifying them according to such a criterion as the legal force of one of them. An analysis of the positions of legal scholars regarding the understanding of the essence and meaning of the category “legal force” has been carried out. The importance of the Constitution of Ukraine, international treaties of Ukraine, as well as the practice of the European Court of Human Rights in the aspect of establishing the legal grounds for detaining a person without a decision of the investigating judge has been emphasized. The laws of Ukraine, including acts of codified legislation, have been considered as a separate group of normative legal acts establishing the legal grounds for detaining a person without a decision of the investigating judge. The shortcomings of the legislative regulation of the legal grounds for detaining a person without a decision of the investigating judge have been emphasized, in connection with which it is proposed to make changes in Art. 29 of the Constitution of Ukraine.

Подчеркнуто, что на сегодняшний день можно назвать достаточно значительное количество нормативно-правовых актов, предписания которых устанавливают правовые основания задержания лица без постановления следственного судьи. Отмечено важность установления сущности правовых оснований задержания лица без постановления следственного судьи и анализ ведущих из них.
Legislative regulation of detention of a person without a decision of an investigating judge
Keywords: законодавча регламентація; затримання без ухвали слідчого судді; кримінальне провадження; нормативно-правовий акт; правові підстави; legislative regulation; detention without a warrant of an investigating judge; criminal proceedings; normative legal act; legal grounds; законодательная регламентация; задержание без постановления следственного судьи; уголовное производство; нормативно-правовой акт; правовые основания